Batrisoplisus Raffray, 1908, a new synonymy of Trisinus Raffray, 1894 (Coleoptera, Staphylinidae, Pselaphinae), with description of three new Chinese species - Yin, Zi-Wei; Nomura, Shûhei; Zhao, Mei-Jun (Zootaxa, 2012)
The genus Batrisoplisus Raffray, 1908 is synonymized with Trisinus Raffray, 1894, with twenty-two new combinations:T. amamianus (Nomura, 1991) comb. n., T. constrictus (Nomura, 1991) comb. n., T. esakii (Nomura, 1991) comb. n., T.galloisi (Jeannel, 1958) comb. n., T. inermis (Nomura, 1991) comb. n., T. monostatos (Nomura, 1991) comb. n., T. oka-motoi (Nomura, 1991) comb. n., T. parallelus (Nomura, 1991) comb. n., T. raffrayi (Jeannel, 1958) comb. n., T.sagamianus (Nomura, 1991) comb. n., T. satsumanus (Nomura, 1991) comb. n., T. sawadai (Nomura, 1991) comb. n.,T. subtilis (Nomura, 1991) comb. n., T. tamino (Nomura, 1991) comb. n., T. tanabei (Nomura, 1991) comb. n., T. tenui-formis (Nomura, 1991) comb. n., T. torticornis (Nomura, 1991) comb. n., T. tosanus (Nomura, 1991) comb. n., T. uroce-ratus brevispinis (Nomura, 1991) comb. n., T. uroceratus uroceratus (Nomura, 1991) comb. n., T. venustus (Jeannel,1958) comb. n. and T. volcaninsulanus (Nomura, 1991) comb. n. Trisinus is recorded for the first time from China. Threenew species from Yunnan Province are described, illustrated and keyed: T. pharelatus Yin & Nomura sp. n., T.shaolingiger Yin & Nomura sp. n. and T. shuixiuifer Yin & Nomura sp. n. A checklist of the world species of Trisinus is provided.